Neoplastic and non-neoplastic swellings of the external genitalia in horses and donkeys: clinical, histopathological, and treatment outcomes - El-Shafaey, El-Sayed; Hamed, Mohammed; Amin, Yahia; Alkhodair, Khalid M.; Shousha, Saad; Aljazzar, Ahmed; El Sebaei, Mahmoud G.; Mosbah, Esam (Frontiers in Veterinary Science, 2025)
AimExternal genitalia swellings represent diagnostic and treatment challenges in equids. Thus, the present study aimed to describe the clinical, histopathological, and treatment outcomes of external genitalia swellings in horses and donkeys.MethodsSeventy-five equids (49 horses and 26 donkeys) from 6 months to 8 years were enrolled based on the clinical evidence of external genital swellings. The descriptive details, including sex, age, lesion location, and treatment outcomes, for each case were recorded and analyzed.ResultsTwenty forms of external genital swellings were recorded and classified into neoplastic (n = 32; 42.67%) and non-neoplastic (n = 43; 57.33%) swellings. The non-neoplastic swellings included inflammatory (n = 30; 69.77%) and non-inflammatory lesions (n = 13; 30.23%). The neoplastic swellings were leiomyoma (4.00%), fibroma (1.33%), fibropapilloma (5.33%), squamous cell carcinoma (9.33%), sarcoid (14.67%), and melanoma (8.00%). The inflammatory forms included pythiosis (9.33%), balanitis (4.00%), posthitis (5.33%), balanoposthitis (6.67%), penile hematoma (2.67%), preputial hematoma (4.00%), orchitis (4.00%), vaginal hyperplasia (1.33%), and vulvitis (2.67%). The non-inflammatory forms involved Bartholin gland cyst (2.67%), persistent hymen (2.67%), hermaphrodite (1.33%), hydrocele (6.67%), and inguinal hernia (4.00%). According to the type of swelling, the treatment protocol was applied, even with conservative or surgical treatment. Sixty-seven cases (89.33%) of the treated animals were completely recovered. However, euthanasia was recommended for three cases (4.00%) with infiltrative neoplastic masses, and five cases (6.67%) died from unrelated causes to the operation.ConclusionAccurate early diagnosis and assessment of the external genitalia swellings can offer veterinarians the opportunity for more precise prognosis and treatment decisions guidance for such challenging cases that affect the reproductive performance of horses and donkeys.